2017
DOI: 10.1590/1981-22562017020.160177
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with the life satisfaction of elderly caregivers of chronically ill and dependent elderly relatives

Abstract: Objective: to compare the life satisfaction of family caregivers, taking into account their gender, age, time since starting care, health, religion, perceived burden and quality of life, and the level of physical and cognitive dependence of the elderly person receiving care, and to investigate the associations between these variables and low life satisfaction. Methods: a total of 148 caregivers in Indaiatuba and Campinas, in the state of São Paulo, Brazil, selected using the convenience method, were interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
1
0
5
Order By: Relevance
“…8 In addition, studies have observed that the amount of care provided and the unmet demands for psychosocial care and assistance in daily living activities were also associated with higher burden of care. 9,10 Studies 8,11 have traditionally documented that life satisfaction is largely influenced by the degree of burden perceived by the caregiver; caregivers with low degree of burden experience high satisfaction, while those with high degree of burden experience low satisfaction. On the contrary, studies have also found that low life satisfaction was significantly associated with high perceived burden, 12,13 indicating a reverse relationship between life satisfaction and burden.…”
Section: Satisfaction With Life and Positive Aspects Of Caregivingmentioning
confidence: 99%
“…8 In addition, studies have observed that the amount of care provided and the unmet demands for psychosocial care and assistance in daily living activities were also associated with higher burden of care. 9,10 Studies 8,11 have traditionally documented that life satisfaction is largely influenced by the degree of burden perceived by the caregiver; caregivers with low degree of burden experience high satisfaction, while those with high degree of burden experience low satisfaction. On the contrary, studies have also found that low life satisfaction was significantly associated with high perceived burden, 12,13 indicating a reverse relationship between life satisfaction and burden.…”
Section: Satisfaction With Life and Positive Aspects Of Caregivingmentioning
confidence: 99%
“…A capacidade adaptativa da família, a força de ligação afetiva, as oportunidades de crescimento pessoal propiciam aos seus membros a capacidade de solucionar problemas, como elementos centrais á boa funcionalidade familiar 29 A proposta de investigar as diferentes intervenções em curto e médio prazo, tais como os grupos de apoio, se elas influenciam positivamente a satisfação com os cuidadores de idosos, mesmo com a presença de fatores negativos, como fragilidade e depressão, é necessária. Nesse sentido, novos estudos são necessários para a produção de subsídios teóricos destinados a estratégias de cuidados, além do aprimoramento de estratégias de autorregulação cognitivo-emocional orientados aos cuidadores familiares de idosos 30 .…”
Section: Estratégias De Enfrentamento Psicológicas No âMbito Individualunclassified
“…Estudiosos revelam que o cuidador familiar é, em sua maioria, do sexo feminino, com idade média de 65 anos e alguém que não teve capacitação específica para ocupar esse papel (Del-Pino-Casado, Millán-Cobo, Palomino-Moral, & Frías-Osuna, 2014;Neri, 2014) o que contribui para muitos desenvolverem uma percepção de sobrecarga moderada a severa, visto que essas pessoas se sentem despreparadas e desamparadas na atividade de cuidar (Caldeira, Neri, Batistoni, & Cachioni, 2017;Neri, 2014;Pinto, 2016). O termo sobrecarga, conhecido internacionalmente como burden, refere-se a um sentimento produzido por contextos nos quais a percepção das demandas decorrentes das atividades de cuidar excede a capacidade de gerenciamento do cuidador, gerando estresse e ansiedade (Alvira et al 2015;Del-Pino-Casado et al, 2014).…”
Section: Introductionunclassified
“…O termo sobrecarga, conhecido internacionalmente como burden, refere-se a um sentimento produzido por contextos nos quais a percepção das demandas decorrentes das atividades de cuidar excede a capacidade de gerenciamento do cuidador, gerando estresse e ansiedade (Alvira et al 2015;Del-Pino-Casado et al, 2014). A falta de suporte familiar associada à renúncia de atividades próprias de trabalho e lazer podem gerar perdas financeiras e sociais, que contribuem, consequentemente, para uma maior sensação de sobrecarga por parte do cuidador e para que conflitos familiares ocorram (Alvira et al, 2015;Caldeira et al 2017;Pinto, Barham, & Del Prette, 2016). Isso pode fazer com que o cuidador apresente menor qualidade de vida quando comparado a não cuidadores após assumir a tarefa de cuidar um familiar idoso (Tomomitsu, Perracini, & Neri, 2014) Além da sobrecarga, a depressão é considerada outro desfecho negativo produzido pela atividade de cuidar de idosos.…”
Section: Introductionunclassified
See 1 more Smart Citation